"Presence" and "Absence": Kaleidoscopic Hide and Seek: Reply to Commentaries. Issue 2 (3rd March 2016) - de Peyer, Janine
Abstract : In this reply I respond to Cambray's introduction of the " self-organizing " and " emergent " qualities of telepathic communication, looking more closely at the relationship between dissociation and the emergence of telepathic phenomena. I highlight the creative aspect of such telepathic "intrusions, " viewing the clinician's capacity for intuitive imagination as key to the emergence of telepathic material. In response to Eshel's connection between the analyst's "presence, " "absence, " and the patient's unmet need for recognition, I examine the roles of co-construction and mutual dissociation in transference-countertransference enactments that generate uncanny phenomena. Verbal interpretation not always being the most viable mode of communication, "absence" can sometimes serve as a co-constructed, unconscious " solution " to the problem of multiple conflicting needs, holding a space for telepathic emergence to express the inexpressable.